A Bivalent Inactivated Vaccine Prevents Enterovirus 71 and Coxsackievirus A16 Infections in the Mongolian Gerbil - Yi, Eun Je; Kim, Young In; Kim, Seung Yeon; Ahn, Sung Hyun; Lee, Hyoung Jin; Suh, Bohyun; Yu, Jaelim; Park, Jeehye; Lee, Yoon Jung; Jung, Eunju; Chang, Sun Young (Biomolecules and Therapeutics, 2023)
Hand-foot-and-mouth disease (HFMD) is a viral infectious disease that occurs in children under 5 years of age. Its main causes are coxsackievirus (CV) and enterovirus (EV). Since there are no efficient therapeutics for HFMD, vaccines are effective in preventing the disease. To develop broad coverage against CV and EV, the development of a bivalent vaccine form is needed. The Mongolian gerbil is an efficient and suitable animal model of EV71 C4a and CVA16 infection used to investigate vaccine efficacy following direct immunization. In this study, Mongolian gerbils were immunized with a bivalent inactivated EV71 C4a and inactivated CVA16 vaccine to test their effectiveness against viral infection. Bivalent vaccine immunization resulted in increased Ag-specific IgG antibody production; specifically, EV71 C4a-specific IgG was increased with medium and high doses and CVA16-specific IgG was increased with all doses of immunization. When gene expression of T cell-biased cytokines was analysed, Th1, Th2, and Th17 responses were found to be highly activated in the high-dose immunization group. Moreover, bivalent vaccine immunization mitigated paralytic signs and increased the survival rate following lethal viral challenges. When the viral RNA content was determined from various organs, all three doses of bivalent vaccine immunization were found to significantly decrease viral amplification. Upon histologic examination, EV71 C4a and CVA16 induced tissue damage to the heart and muscle. However, bivalent vaccine immunization alleviated this in a dose-dependent manner. These results suggest that the bivalent inactivated EV71 C4a/CVA16 vaccine could be a safe and effective candidate HFMD vaccine.
Keywords: Bivalent vaccine; Coxsackievirus A16; Enterovirus 71; Gerbil; Hand-foot-and-mouth disease